Temporary agency work in Portugal, 1995 - 2000 - René Böheim; Ana Rute Cardoso (Institute for the Study of Labor (IZA), 2007)
There is widespread belief that workers in temporary agency work (TAW) are subject to poorer working conditions, in particular pay, than comparable workers in the rest of the economy. The first aim of this analysis is to quantify the wage penalty, if any, for workers in TAW. Secondly, we analyze the wage profile of workers before and after spells of TAW. Linked employer-employee data for Portugal enable us to account for observable as well as unobservable worker quality. Our results show that workers in TAW earn lower wages than their peers and that this difference is mostly due to the workers' characteristics. We estimate that workers in TAW earn on average 9% less than comparable workers in the rest of the economy if we control for the workers' observable attributes only; this difference is reduced to 1% when we control for unobservable characteristics as well. However, interesting differences emerge across groups. Younger workers, both men and women, earn higher wages in TAW than their peers in other firms, as opposed to prime-age and older workers. Moreover, for young workers TAW is not associated with a stigma effect that slows wage progression after working for TAW, contrary to prime-age and older workers, in particular males. The wage trends are also different before entering TAW. Prime-age and older workers see their wages deteriorate relative to their peers before entering TAW, suggesting that adverse labor market conditions may motivate them to search for a TAW job. We do not detect any pre-TAW wage trend for young workers.
Keywords: 330; Temporary work agencies; temporary help service; matched employer-employee data; Portuguese labor market; Leiharbeit; Lohnstruktur; Qualifikation; Altersgruppe; Lohndifferenzierung; Portugal